Genome-wide landscape of genetic diversity, runs of homozygosity, and runs of heterozygosity in five Alpine and Mediterranean goat breeds - Sara Pegolo; Vittoria Bisutti; Lucio Flavio Macedo Mota; Alessio Cecchinato; Nicolò Amalfitano; Maria Luisa Dettori; Michele Pazzola; Giuseppe Massimo Vacca; Giovanni Bittante (Journal of Animal Science and Biotechnology)
Abstract Background Goat breeds in the Alpine area and Mediterranean basin exhibit a unique genetic heritage shaped by centuries of selection and adaptability to harsh environments. Understanding their adaptive traits can aid breeding programs target enhanced resilience and productivity, especially as we are facing important climate and agriculture challenges. To this aim the genomic architecture of 480 goats belonging to five breeds (i.e., Saanen [SAA], Camosciata delle Alpi [CAM], Murciano-Granadina [MUR], Maltese [MAL], Sarda [SAR]) reared in the Sardinia Island were genotyped and their genomic architecture evaluated to find molecular basis of adaptive traits. Inbreeding, runs of homozygosity (ROH) and runs of heterozygosity (ROHet) were identified. Finally, candidate genes in the ROH and ROHet regions were explored through a pathway analysis to assess their molecular role. Results In total, we detected 10,341 ROH in the SAA genome, 11,063 ROH in the CAM genome, 12,250 ROH in the MUR genome, 8,939 ROH in the MAL genome, and 18,441 ROH in the SAR genome. Moreover, we identified 4,087 ROHet for SAA, 3,360 for CAM, 2,927 for MUR, 3,701 for MAL, and 3,576 for SAR, with SAR having the highest heterozygosity coefficient. Interestingly, when computing the inbreeding coefficient using homozygous segment (F ROH), SAA showed the lowest value while MAL the highest one, suggesting the need to improve selecting strategies to preserve genetic diversity within the population. Among the most significant candidate genes, we identified several ones linked to different physiological functions, such as milk production (e.g., DGAT1, B4GALT1), immunity (GABARAP, GPS2) and adaptation to environment (e.g., GJA3, GJB2 and GJB6). Conclusions This study highlighted the genetic diversity within and among five goat breeds. The high levels of ROH identified in some breeds might indicate high levels of inbreeding and a lack in genetic variation, which might negatively impact the animal population. Conversely, high levels of ROHet might indicate regions of the genetic diversity, beneficial for breed health and resilience. Therefore, these findings could aid breeding programs in managing inbreeding and preserving genetic diversity.